The great name : ancient Egyptian royal titulary - Leprohon, Ronald J.; Doxey, Denise M. (2013)
This volume includes all rulers' names, from a single original name through the growth of the five-fold titulary, from the so-called Dynasty 0 to the last Ptolemaic ruler, offered in transliteration and English translation with an introduction and notes.
Includes bibliographical references (pages 243-260) and indexes.
Keywords: Titles of honor and nobility -- Egypt -- History -- To 1500.; Egypt -- Kings and rulers -- Titles; Egypt -- History -- To 332 B.C.; Egypt -- History -- 332-30 B.C.